Peran Citra Merek Dan Hubungan Emosional Dalam Membangun Loyalitas Konsumen Pada Produk Samsung - Lintang Khaerunisa; Ahmad Bagja Abdillah; Rifa Hasna Hanifah; Helin G Yudawisastra (Journal of Literature Review, 2026)
This study aims to analyze the role of brand image and emotional relationship on consumer loyalty toward Samsung smartphone products while maintaining product quality. The increasingly competitive smartphone industry requires companies not only to focus on product quality but also to build a strong brand image and create emotional bonds with consumers. This research employs a qualitative approach using a document study method by reviewing and analyzing relevant scientific journals and literature related to the research topic. The findings indicate that a positive brand image shapes consumer perceptions and trust in Samsung products, while emotional relationships formed through product usage experiences strengthen consumer loyalty. Although product quality remains an important factor, consumer loyalty becomes stronger when supported by a favorable brand image and emotional attachment. This study is expected to contribute theoretically to marketing studies and provide insights for companies in formulating strategies to enhance consumer loyalty.